Narration the Lived Experiences of Career Couples of Family Function, Health Dimension - Rohollah Rahimi; Hossien Salimi Bajestani; Kiumars Farahbakhsh; Mohammad Asgari (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2020)
Introduction: Family function has been changed by the couple's simultaneous employment and presents particular problems for the family and the couples. One of the dimensions that is strongly influenced by the functioning of the working couple's family is the health dimension. The purpose of this study was to extract living experiences of career couples from the health aspect of family functioning. Methods: This research was done by qualitative approach and by the method of interpretive phenomenology. In this study, the researchers selected and interviewed 12 career couples with snowball sampling and 12 career couples with marital conflicts through purposeful sampling. Interviews were analyzed using the Dicklman, Allen, and Turner methods, which are team-based and common in interpretive phenomenology. The MAXQDA12 software was also used for these operations. Results: The analysis of the data from the interviews resulted in the identification of two main themes, including healthy functioning (with sub-themes: psychological functions of employed women, psychological functions of career couples, social functions of employed women, social functions of career couples, and spiritual health) and unhealthy functioning. (with sub-themes: physical damage, psychological damage, social damage, spiritual damage). Conclusion: The findings of this study showed that simultaneous employment of couples has a two-way effect on their health. On the negative side, this threatens the overall physical, psychological, social and spiritual health of the couple. On the positive side, the desirability of work conditions, couples' perceptions and attitudes have the greatest impact on health as one of the important dimensions of family function of career couples.